2012
DOI: 10.1002/aic.13776
|View full text |Cite
|
Sign up to set email alerts
|

Data‐based linear Gaussian state‐space model for dynamic process monitoring

Abstract: This article develops a data‐based linear Gaussian state‐space model for monitoring of dynamic processes under noisy environment. The Kalman filter is introduced for construction of the linear Gaussian state‐space model, and an iterative expectation‐maximization algorithm is used for model parameters learning. With the incorporation of the dynamic data information, a new fault detection and identification approach is proposed. The feasibility and effectiveness of the two monitoring statistics in the new method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The RBC for each sample and each variable is drawn by a color tape, where the darker color represents the higher RBC. From the plot, it is observed that variables 18 and 19 are indeed the most significant candidates for this fault, which is consistent with the conclusions in [15] and [24]. However, traditional dynamic methods such as DPCA, SIM, and CVA do not reveal a structure in the lagged variables, which makes the diagnosis analysis difficult to implement.…”
Section: Case Study On the Tepsupporting
confidence: 87%
See 2 more Smart Citations
“…The RBC for each sample and each variable is drawn by a color tape, where the darker color represents the higher RBC. From the plot, it is observed that variables 18 and 19 are indeed the most significant candidates for this fault, which is consistent with the conclusions in [15] and [24]. However, traditional dynamic methods such as DPCA, SIM, and CVA do not reveal a structure in the lagged variables, which makes the diagnosis analysis difficult to implement.…”
Section: Case Study On the Tepsupporting
confidence: 87%
“…For multiple indexes in a method, if any statistic exceeds its control limit, the fault is detected. From the FDRs for all faults (except IDV 3,9,15), it can be seen that the DLV-based method can detect faults more stably than DPCA and outperforms PCA and SIMbased methods in most cases. Although CVA-based method has a higher FDR, its FAR is also high, which is caused by the inversion of the small values of R 0 in (8).…”
Section: Case Study On the Tepmentioning
confidence: 92%
See 1 more Smart Citation
“…(12)- (16) are calculated through the iterative manner. When t = 1, the initial value of f 1 and F 1 are given as…”
Section: Learning Supervised Lds Model Via Em Algorithmmentioning
confidence: 99%
“…For the fault detection purpose, the LDS model has already been introduced. For example, a data-based linear Gaussian state-space model was constructed upon the framework of LDS for dynamic process monitoring [16], a switching LDS-based approach has been proposed for fault detection and classification [17].…”
Section: Introductionmentioning
confidence: 99%